Evaluation of Homeopathic Phosphoric Acid, Silica and Pathogenic Vibrio on Digestive Enzyme Activity of Longfin Yellowtail Fish (Seriola rivoliana) - Mazón-Suástegui, José Manuel; Salas-Leiva, Joan; Teles, Andressa; Tovar-Ramírez, Dariel (Homeopathy, 2020)
Background This research aimed to observe the effect of homeopathically prepared Vibrio parahaemolyticus (ViP) and V. alginolyticus (ViA) and the commercial homeopathic compound Similia (Phosphoricum acidum and Silicea terra) on the digestive enzyme activities of Seriola rivoliana juveniles under usual culture conditions.Materials and Methods Biochemical analysis was used to study the effect of highly diluted substances (7C potency) prepared from ViP and ViA (Treatment 1: T1) and the homeopathic compound Phosphoricum acidum and Silicea terra (Treatment 2: T2) on changes in the main digestive enzymes on weaning-state fish (WS; 30 days post-hatching [DPH]) and early juveniles (EJ; 62 DPH) versus a reference control group that received no homeopathic medicines.Results Treatment T2 significantly increased the activity of trypsin and lipase and decreased the activity of amylase, whereas treatment T1 increased the activity of chymotrypsin and reduced the activity of aminopeptidase-N in WS fish. Except for alkaline phosphatase, which was significantly reduced in the intestine, no significant differences in enzymatic activity were found between treated EJ fish and controls. The fish of the WS group had a higher growth rate with the T2 treatment.Conclusions T1 treatment stimulated chymotrypsin in EJ fish and T2 promoted intestinal maturation of WS fish. Higher growth rate with the T2 treatment may be associated with the stimulation of trypsin activity. Thus, T2 may be applied, under hatchery conditions, during larval stages with an aim to enhance digestion and assimilation of inert food.
Keywords: aquacultural homeopathy; Seriola rivoliana; digestive enzymes; gut maturation